Pemaknaan Identitas Gender pada Pemain Crossgender dalam Mobile Game Toram Online Indonesia - Hira Askamal; Hendriyani Hendriyani (Asosiasi Pendidikan Tinggi Ilmu Komuniasi (ASPIKOM) Wilayah Riau, 2021)
The presence of avatar features in mobile online team games where most male players use femalecharacters with attractive appearance, which can be referred to as crossdressers in the real world,and look like cross-gender or home activities in online games. Besides, various speculations havealso arisen about their cross-gender goals and being a place to live. The formulation of this studyproblem is how the definition of gender identity in cross-gender players in mobile games toramonline Indonesia. This result research method was carried out with a phenomenological approach,the data collected through interviews and participants' observations. The results showed that playersshape their identity into women based on their background, such as the potential benefits gained orbecause of an experience experienced as a result of gender stereotypes that occur in the game. Coderefers to players who create female characters and seek to shape their image as women, whileplayers who do not have such meaning cannot be said to be home even though they are the samemale players who use female characters. The potential benefits obtained can be information, items,money in the game, and the player's personal pleasure in acting and shaping his identity.